Adipose tissue NK cells manifest an activated phenotype in human obesity - O’Rourke, Robert W.; Gaston, Garen D.; Meyer, Kevin A.; White, Ashley E.; Marks, Daniel L. (Metabolism, clinical and experimental, 2013)
Adipose tissue inflammation is a cause of obesity-related metabolic disease. Natural killer (NK) cells are an understudied cell type in the context of obesity. The goal of this study was to determine the phenotype of human adipose tissue NK cells. We used flow cytometry phenotyping to study adipose tissue and peripheral blood NK cells from obese and lean humans. Human adipose tissue NK cells, relative to peripheral blood NK cells, express increased levels of activation markers. Adipose tissue NK cells also demonstrate an activated phenotype in obese relative to lean subjects, with increased expression of the activating receptor NKG2D. These data are the first detailed phenotypic characterization of human adipose tissue NK cells, and suggest a role for NK cells in adipose tissue inflammation in obesity.